A nonlinear BE formulation for analysis of masonry walls considering orthotropy: Fundamentals. (October 2021) - Oliveira Neto, Luttgardes de; Masia, Mark John; Almeida, Valério S.; Simonetti, Hélio Luiz
Abstract: In this work, a non-linear Boundary Element (BE) formulation with damage model is extended for numerical simulation of structural masonry walls. The original formulation was presented by other researchers to investigate the concrete material in 2D stress analysis. The formulation proposal is written in terms of domain strain variables and it is based on the consistent tangent operator. A simple damage model is used to represent the material behavior of masonry components and internal variables and cell discretization of the domain are considered. However, for brick masonry it is necessary to take into account the orthotropy in this type of structure. The orthotropy is considered by expressing a residual elastic tensor as the difference of the orthotropic and the isotropic elastic property tensors. The complete integral formulation, using isotropic fundamental solution, and algebraic procedure are developed.